CRITICAL THINKING EFFECTIVE EDUCATION RESOURCES MANAGEMENT DURING THE CRISIS OF THE 21st CENTURY - Amalliah Kadir (J-ABDI: Jurnal Pengabdian kepada Masyarakat, 2022)
In general, there is a wide gap in the quality of education between education in our country and the quality of education in developed countries, although in some individual achievements at the international level, Indonesian children are able to excel. The wide gap in the quality of education in Indonesia is reflected, among other things, from the results of a study on reading ability for elementary school (SD) conducted by the International Educational Achievement (IEA) organization which conducted a research called Trend in International Mathematics and Sciences Study (TIMSS) in in 1999 which indicated that elementary school students in Indonesia were in 38th place out of 39 countries studied. Meanwhile, for junior high school (SMP) level, the study for mathematics ability of junior high school students in Indonesia was only 39 out of 42 countries studied, and natural science (IPA) skills only ranked 40 out of 42 countries studied. In 2003, the same research was conducted. To catch up with education, the government launched a superior school policy. This policy is expected to be able to improve the quality of education, especially schools. This policy is stated in the Strategic Plan of the Ministry of National Education 2010-2014, namely by doing: 1. Development of local excellence-based schools in each district/city. 2. Construction of quality schools commensurate with international education management in each province/district/city. Before the policy of superior schools proclaimed by the government was set, actually schools that could be categorized as superior schools had been scattered in this country, unfortunately most of them were scattered in big cities. Until 2020, the survey results prove that the State of Indonesia is in 10th place from the bottom with other countries in terms of literacy and science. This article uses library research methods from books and journals, aiming to find out how effective HR quality is in 21st century education unit management.